Micro-explosion and autoignition of composite fuel/water droplets; Combustion and Flame; Vol. 210 - Antonov D. V. Dmitry Vladimirovich; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Rybdylova O. Oyuna; Sazhin S. S. Sergey Stepanovich (2019, 2019)
Title screen